Physical disability and well-being - Crawley, Thomas (2021)
It is commonly assumed that physical disability makes life worse, for reasons other than society’s unjust treatment of disabled people. Both laypersons and philosophers have typically taken physical disability itself to be a significant detriment to well-being. However, this common view of physical disability has been challenged recently. Beginning with the Social Model in the 1970s, disabled people and disability rights campaigners have increasingly rejected the so-called ‘Bad-Difference View’ (BDV) of physical disability in favour of the so-called ‘Mere-Difference View’ (MDV). The MDV says that physical disability is akin to gender and race in that, if we discount the effects of unjust discrimination, it does not make someone worse (or better) off. This thesis offers a sustained and detailed examination of the debate between the MDV and the BDV. It characterises the best understandings of the views, explains how to determine their truth values, examines prominent arguments for both, presents new arguments, and brings this all together to present a defeasible argument for a BDV of physical disabilities. Finally, it suggests a novel direction that the debate between the MDV and the BDV might take.